Genetic Analysis for Relationships between some Native Sour Cherry (Prunus cerasus l.) Using RAPD Markers - Ioana Virginia BERINDEAN; Alexandra Maria ITU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2019)
Prunus cerasus L. are an allotetraploid species from temperate climatic zone. The aim of this study was to characterize some native sour cherry genotypes from different orchards from Romania, based on RAPD markers. We used 14 primers RAPD to analyze a total of 14 varieties of sour cherries. After analysis, a good level of polymorphism was generated about only six primers (OPA 04, OPB10, OPA17, OPA20, OPA03 and OPB17) the rest of primers were considered monomorphic. The dendrograme separated the cultivars according to their genetic and geographic origin. The genetic similarity among the cultivars showed a good diversity between the genotypes, so we can suggest that our native cultivars of sour cherry can be considered as distinct genotypes for futures breeding programs and new cultivar identification. Results also confirm that the RAPD primers can be used for genetic studies and to evaluate the varieties for breeding programs.